Equipment Design in the Design of Industrial Products (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
From the beginning of the design until now, in order to produce a consumer product of various complexity, it is necessary to draw up its necessary project. It is natural that many errors appear in the design, shape and even style of the product created without a necessary project. The project composition and design of the product allows to match the exact dimensions of the manufactured item, to fully study the volumetric shape and design aspects of the product, and to perceive the shape of the product as an object.This article talks about the importance and production of furniture products in industrial design.